PENGARUH EKSTRAK DAUN SIRIH (PIPER BETTLE LINN.)TERHADAP EFEK SEDASI MENCIT (MUS MUSCULUS L.)DAN SUMBANGANNYA PADA PEMBELAJARAN BIOLOGI SMA - Siti Rakhmi Afriani; Riyanto Riyanto; Kodri Madang (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2016)
Abstract: This study research aims to determine the effect of extracts of betel leaf (Piper bettle Linn.) For sedation mice (Mus musculus L.). The method is used the experimental method with completely randomized design (CRD), which consists of 4 treatments and 6 replications. The treatment consisted of a negative control group (distilled water), and three groups of mice were given extracts of betel leaf with each dose of 0.5 mg / 10 gBW, 1 mg / 10 gBW, and 2 mg / 10 gBW. Data were analyzed by calculating the Diversity Analysis and continued with Test BNT. To decrease muscle power with Traction Test method, then a decreased activity and sensitivity to the environment with Fireplace Test method. Diversity analysis results indicate that the betel leaf extract significant effect on the increase in sedation mice, decreased muscle power, then a decreased activity and sensitivity to the environment with Fireplace Test method. BNT test results show that betel leaf extract dose of 0.5 mg / 10 gBW is the most effective dose in mice increases sedation. Information on the results of this study can be alternatif examples for learning and teaching material and contribution to the Learning Class XI Biology Semester II Basic Competence 3.10. Key Words:Piper bettle Linn., Sedation, Mus musculus L.